Translation and quality - Schäffner, Christina (Current issues in language and society (Unnumbered), 1998)
The whole basis of quality in relation to translations is considered in this well argued set of essays. The emphasis is on an honest discussion of training needs and the use of examples to illustrate the points that the contributors make.